A TALE OF TWO OKC’S : CLINICAL INSIGHTS FROM PEDIATRIC AND ADULT PRESENTATIONS - Andini, Putri; Epsilawati, Lusi; Pramanik, Farina; Medika, Chrisna Ardhya (Universitas Muhammadiyah Semarang, 2025)
Background: Odontogenic Keratocyst or OKC is one of the odontogenic cysts of the jaw. Its prevalence is greater in the lower jaw. OKC radiographically appears with unicystic or multicystic lesions. To be able to recognize it in a radiograph is very difficult and sometimes causes difficulties. The most special thing about this lesion is that it has a shallop border, enlarges by walking along the bone and tissue causing resorption of the roots of the involved teeth. Case: there are two cases that have similarities between each other. First case: An 11-year-old girl came to the radiographic installation for a panoramic examination, with swelling in right mandible since 8 months ago. Second case: A 32-year-old woman came to do a panoramic examination. Patient complaints of swelling in the mucosa of lower mandible since 6 months ago. Both cases were diagnosed as Odontokeratocyst (OKC). Conclusion: OKC basically has a quite different appearance in radiographs. This difference is easily recognized specifically in both cases in children and adults. This difference can be known from the characteristics of the growth type, scallop borders and minimal resorption of the tooth roots. However, OKC has a high recurrence rate. Panoramic radiography is quite capable of showing all the differentiating characteristics needed.